2013
DOI: 10.1371/journal.pone.0063325
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Agonistic and Blocking Effects of CD200 Receptor Antibodies

Abstract: The CD200 receptor (CD200R) is present mainly on myeloid cells and gives inhibitory signals when engaged by its ligand CD200. The interaction is currently of therapeutic interest in cancer and inflammation. However functional effects are complicated by the fact that CD200R is itself polymorphic and also a member of a paired receptor family with four closely related gene products in mice called CD200RLa etc. We show that a second allele of CD200R (termed CD200R(2)) that differs in 7 amino acids also binds CD200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…This suggests that the engineering of the NOD SCID mouse with human CD200R may improve the efficacy of grafting. The CD200R does not show the same degree of polymorphism as SIRP α with only two alleles identified that differ in seven amino acids …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This suggests that the engineering of the NOD SCID mouse with human CD200R may improve the efficacy of grafting. The CD200R does not show the same degree of polymorphism as SIRP α with only two alleles identified that differ in seven amino acids …”
Section: Discussionmentioning
confidence: 94%
“…The CD200R does not show the same degree of polymorphism as SIRPa with only two alleles identified that differ in seven amino acids. 29 One additional feature in this interaction is that there can be some 'education' of the sensitivity of the SIRPa on macrophages, as indicated by studies on CD47 knockout mice. Hence CD47 À/À red blood cells are removed when injected into wild-type mice but this does not seem to happen in the CD47 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting receptor-ligand interactions has become increasingly important, as indicated by CD200/ CD200 receptor (CD200R) in leukemia cells and CD47/SIRP in many cancers cells [11,[25][26][27]. We developed a peptide inhibitor targeting the CD200R isoform activation receptors [4].…”
Section: Cd200 Inhibitor Blocks Immune Suppression From Tumor-derivedmentioning
confidence: 99%
“…The identification of eight different immune cell populations using the phenotyping Abs, adapted from a published strategy (23) is shown (Fig. 6b).…”
Section: Resultsmentioning
confidence: 99%